2018
DOI: 10.1002/hep.29756
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes in cirrhosis: A scoping review of the literature

Abstract: This scoping review identified and categorized a large existing set of PRO concepts that matter to patients with cirrhosis; these outcomes may now be translated into usable measures both for the assessment of the quality of cirrhosis care in clinical practice and to perform research from the patient's perspective. (Hepatology 2018;67:2375-2383).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 23 publications
1
98
0
2
Order By: Relevance
“…The working group performed a scoping review of literature to identify a comprehensive set of patient‐reported outcomes for inclusion in the candidate measures. The results of this review are published elsewhere . The working group then reviewed the list of candidate outcome measure and identified additional outcomes that captured the clinical status of patients with cirrhosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The working group performed a scoping review of literature to identify a comprehensive set of patient‐reported outcomes for inclusion in the candidate measures. The results of this review are published elsewhere . The working group then reviewed the list of candidate outcome measure and identified additional outcomes that captured the clinical status of patients with cirrhosis.…”
Section: Methodsmentioning
confidence: 99%
“…Most complications require hospitalization, and nearly 70% of patients are readmitted within 1 year, costing more than $20,000 per admission . The burden of cirrhosis is amplified by its dramatic impact on quality of life, resulting from multiple physical, psychological, cognitive, and social stressors …”
mentioning
confidence: 99%
“…In addition to clinical decompensations, cirrhosis is also associated with poor patient‐reported outcomes (PROs) such as poor sleep and diminished health‐related quality of life (HRQOL). We recently reviewed the determinants of PROs in cirrhosis . Like others, we found that liver disease severity, particularly HE, is the principal driver of symptoms and poor HRQOL .…”
mentioning
confidence: 62%
“…The lived experience of cirrhosis can be very challenging for many patients, marked by debilitating symptoms and poor HRQOL . Poor PROs have been traditionally associated with cirrhosis complications such as ascites and overt HE .…”
Section: Discussionmentioning
confidence: 99%
“…These include muscle cramps, pruritus, sleep disturbances, and sexual dysfunction that can improve with symptomatic treatment(12). Patients may not disclose these concerns in a busy clinic visit, so they should be proactively assessed by providers.…”
Section: “Dos and Don’ts” In The Clinic (Table 2)mentioning
confidence: 99%